Ṭarīqah al-Mubāsyarah dalam Pembelajaran Mahārah al-Kalām di Kelas I KMI Pondok Modern Arrisalah Ponorogo - Rohman, Addib Ngabdul; Muqorrobin, Syamsul; Ana, Sri (Study Program of Arabic Language Teaching, 2021)
The title of this paper is Al-Ṭarīqah Al-Mubāsyarah in Mahārah Al-Kalām Learning in Class 1 KMI Pondok Modern Arrisalah Ponorogo. This study aims to determine Al-Ṭarīqah Al-Mubāsyarah in Mahārah Al-Kalām learning, the factors that influence it, and the advantages and disadvantages in its application. This was a case study qualitative research. In this qualitative research, interviews, observations, and documentation were used to collect data. The analysis in this study used data reduction, data display, and conclusion. The result of this research is the application of Mahārah Al-Kalãm Arabic learning using the direct method are divided into three stages: preparation, implementation, and evaluation. The advantages of learning Mahārah Al-Kalm with the direct method are: (1) the teacher is easy to convey the material; (2) the students are active in learning; and (3) it is easy to measure learning outcomes. The weaknesses of learning Mahārah al-Kalām with the direct method are: (1) it takes a lot of time; (2) it lacks detail in the material; and (3) the teacher cannot focus on one aspect.